Membrane Protein 4F2/CD98 Is a Cell Surface Receptor Involved in the Internalization and Trafficking of Human β-Defensin 3 in Epithelial Cells. Issue 2 (19th February 2015) - Colavita, Irene; Nigro, Ersilia; Sarnataro, Daniela; Scudiero, Olga; Granata, Vincenzo; Daniele, Aurora; Zagari, Adriana; Pessi, Antonello; Salvatore, Francesco
Summary: Human β-defensins play a pivotal role in the innate immune response. Although expressed by and acting at epithelial surfaces, little is known about their specific interaction with epithelial structures. Here, we identify the transmembrane protein CD98 as a cell surface receptor involved in the internalization of human β-defensin 3 (hBD3) in human epithelial A549 cells. CD98 and hBD3 extensively colocalize on the basolateral domain of A549. While verifying their direct binding by fluorescence resonance energy transfer and surface plasmon resonance, we mapped the interaction to CD98 residues 304–414, i.e. to the region known to interact with the proteins of intestinal bacteria during colonic invasion. Treatment of A549 cells with hBD3 dramatically reduces CD98 expression and conversely, knockdown of CD98 expression impairs hBD3 cell surface binding and internalization. Competition for bacterial binding to CD98 and downregulation of CD98 expression may represent novel mechanisms for the antibacterial activity of hBD3. Graphical Abstract: Highlights: Proteomics of hBD3 at the cell surface indicates that CD98 is a receptor hBD3 reduces CD98 expression in epithelial cells Trafficking into epithelial cells occurs through recycling endosomes hBD3 binding to CD98 with high affinity may represent a novel antibacterial mechanism Abstract : Colavita et al. show that CD98 is a receptor that mediates hBD3 internalization in epithelial cells. The region involved in hBD3 binding overlaps with the area known to interact with intestinal bacteria. This suggests a novel mechanism of antibacterial action for defensins.